ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR ACUTE MYELOID LEUKEMIA OF THE ELDERLY: REVIEW OF THE LITERATURE AND PERSPECTIVES. - Gabriele Magliano; Andrea Bacigalupo (Mediterranean Journal of Hematology and Infectious Diseases)
Acute myeloid leukemia (AML) in adults older than 60 years old has a poor prognosis. Elderly patients often present with comorbidities and an adverse biology of the disease, with higher genetic risk and chemoresistance.  Allogeneic hematopoietic stem cell transplantation (HSCT) can be an effective treatment, and can improve overall survival (OS).Intensive chemotherapy (IC) before HSCT and  myeloablative conditioning regimens can produce significant toxicity and transplant-related mortality (TRM). Reduced-intensity conditioning (RIC) or non-myeloablative (NMA) regimens appear to preserve the graft-versus-leukemia effect, and may improve survival. The increasing knowledge in  AML of the elderly  is  currently being associated with  a multidimensional approach to identify those patients eligible for targeted therapy, such as Flt3 inhibitors, and/or allogeneic HSCT.